Generation Z's binge-watching lifestyle in using Over-The-Top (OTT) media services in Indonesia - Edy Prihantoro (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indonesia is the country with the highest Over-The-Top (OTT) media consumption in Southeast Asia. The consumption of OTT media grows by 40% every year. The existence of OTT media has raised the binge-watching phenomenon. This research focuses on how Generation Z's binge-watching lifestyle uses OTT media. This research uses a qualitative methodology by conducting a Focus Group Discussion (FGD) with four to six informants from six regions in Indonesia who actively use OTT media. The theory used in this research is the Media Ecology Theory. Results show that Generation Z watches movies they like more than three hours daily. They determine the duration, frequency, and platforms they want to use. Generation Z's motivations for binge-watching are pleasure (as a medium of entertainment and relaxation), efficiency (easy to access), control (having low self-control), fandom (wanting to feel close to the player), and recommendations from others (not being left behind by others). Binge-watching positively impacts by providing a more open perception of experience, thoughts, and points of view. However, binge-watching has negative impacts, such as lack of sleep and increased imagination. OTT media is advised to provide hourly reminders to viewers to pause while binge-watching.